Desarrollo de una aplicación móvil para el control de alimentación y medicación en pacientes con diabetes tipo 2 mediante inteligencia artificial en la clínica San Luis. - Gallo Monsalve, Kevin Josué (2024)
The current research project consists of implementing an application with artificial intelligence for mobile devices with Android OS to record and monitor the treatment of patients with type 2 diabetes. This topic is based on conducted research and surveys on patients of San Luis Clinic. The main objective is to develop a mobile application with artificial intelligence that allows to register the patients' examinations, so that the artificial intelligence prescribes and notifies the respective medicines and food that the patient should consume on the indicated dates by the doctor through a mobile application. In addition, all patients will be able to mark the consumed food and the medicines in such way that they will be saved in the database to keep track, patients will also be able to visualize their type 2 diabetes levels through a graph of results based on the performed tests from the application. The presented results are of great benefit to patients and doctors because they will have the application on their cell phones. Moreover, they will be able to consult and record the patient's information whenever they need it. This project focuses on the development of a mobile application that uses artificial intelligence (AI) to help patients with type 2 diabetes by facilitating the management of their condition at San Luis Clinic. The Scrum methodology with its iterative and flexible approach was used in order to manage, control, and execute this project.